MATHEMATICAL MODEL OF THE UAV MOTOR FOR REAL TIME SIMULATION - Larkov, Serhii (SWorld-Ger Conference proceedings, 2023)
The paper describes the development of a fast computational mathematical model of a UAV propeller installation for flight simulation in real time